PERAN BAITUL MAAL HIDAYATULLAH GERAI PROBOLINGGO DALAM PEMBERDAYAAN MASYARAKAT - Hasanah, Uswatun; Pertiwi, Fia Ayuning (LPPM STAI Muhammadiyah Probolinggo, 2022)
According to the language zakat comes from the root word (masdar) from zakka which means blessing, growing, clean and good. Zakat means thaharah (clean), growth and barakah. This is in accordance with the word of Allah in Sura al-Tawbah verse 103. While the meaning of zakat shari'i is: